1984
DOI: 10.1111/j.1651-2227.1984.tb17782.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Transcephalic Impedance, Head Growth and Caloric Intake to Outcome in Preterm Infants

Abstract: Twenty-two preterm infants with birth weights less than 1 400 g were measured weekly with transcephalic impedance and occipital-frontal head circumference. Mean caloric intake/kg/day was calculated weekly. All infants were assessed at one year of age with Bayley Mental and Motor Scales and neurological assessment. Univariate and multivariate analyses were performed indicating that transcephalic impedance was the most powerful of the three measures as a predictor of sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…38 Another study examined myelination, measured by transcephalic impedance, and found relationships with developmental scores. 39 In smaller samples, HC in children born with VLBW was found to correlate with later cognitive abilities. 40 More recently, Cheong et al evaluated 202 preterm infants using HC, MRI and Bayley scores at age 2 years.…”
Section: Discussionmentioning
confidence: 96%
“…38 Another study examined myelination, measured by transcephalic impedance, and found relationships with developmental scores. 39 In smaller samples, HC in children born with VLBW was found to correlate with later cognitive abilities. 40 More recently, Cheong et al evaluated 202 preterm infants using HC, MRI and Bayley scores at age 2 years.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple scientific studies have shown the importance of caloric intake within proper neurodevelopment. Caloric deprivation has been found to be a significant risk factor [ 30 ] as work has shown that infants with slower head growth often have lower caloric intake levels [ 31 ]. Continually, a positive association has been highlighted between nutrition and brain volume with nutritional intake having the largest statistically significant impact on brain volume [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the work done on human cerebral EBI in adults in the fields of electrical impedance tomography (Yerworth et al 2003, Romsauerova et al 2006, stroke (Liu et al 2006, Bonmassar et al 2010, rheoencephalography (Bodo 2010), or in neonates (Ellison et al 1984, Weindling et al 1983, Siddiqi et al 1980, Reigel et al 1977 has been performed mostly using single frequency, there is no other source of cerebral EBIS data to enable any reasonable comparison. From the studies performed on neonates (Ellison et al 1984, Weindling et al 1983, Siddiqi et al 1980, Reigel et al 1977, the only comparable information is that all the studies share the same methodology for placing the electrodes.…”
Section: Electrical Bioimpedance Cerebral Monitoringmentioning
confidence: 99%